Organo-Silica Membrane Prepared from TEOS-TEVS Modified with Organic-Acid Catalyst for Brackish Water Desalination - Elma, Muthia; Lestari, Aptar Eka; Sumardi, Anna; Assyaifi, Zaini Lambri; Darmawan, Adi; Mujiyanti, Dwi Rasy; Syauqiah, Isna; Rahma, Aulia; Suciwati, Linda; Mawaddah, Yanti (Jurnal Rekayasa Kimia & Lingkungan, 2021)
The sol gel process is one of the processes used in the manufacture of thin films on membranes because it can control the pore size in the resulting silica matrix. In addition, another way to build membrane size can be done by adding catalysts and precursors to be used. In this study, using a combination of tetraethyl ortho silicate (TEOS) and triethoxy vinyl silane (TEVS) precursors and citric acid as a catalyst to produce a silica matrix with mesoporous size so that it is suitable for application in the desalination process. The organo silica membrane was calcined at 350 C for 1 hour using the RTP calcination technique under vacuum, thus preventing the decomposition of carbon in the silica matrix. The membrane was dipcoated 4 times to obtain 4 layers. The FTIR (Fourier-transform Infrared Spectroscopy) test was carried out to see the functional groups on xerogel, namely silanol, siloxane and carbon. In addition, the performance of this membrane is carried out by desalination through pervaporation using 0.3% NaCl feed water with variations in feed air temperature, namely 25, 40and 60. The resulting flux of air value increased with increasing feed water temperature, namely 6.1; 11.2; and 12.1kg.m-2h-1while the resulting salt rejection was 99.72; 99.64 and 99.23%. So that the organo silica membrane is suitable when applied to the desalination process through pervaporation.